ANALISIS RELIABILITY DAN AVAILABILITY MESIN PABRIK KELAPA SAWIT PT. PERKEBUNAN NUSANTARA 3 - Yuhelson Yuhelson; Bustami Syam; Sukaria Sinullingga; Ikhwansyah Isranuri (Jurnal Dinamis, 2010)
AbstractThis study presents a case study describing reliability and availability analysis of CriticalMachine at the Rambutan Palm Oil Factory of PTP Nusantara 3. The failures data ofengineering system were analyzed by Pareto’s Diagram, and the critical machine was foundedis Screw Press. Screw Press is consist of seven critical subsystems i.e: Left & Right HandedWorm, Bushing, Press Cylinder, Rebuild Worm, Bearing SKF 29326, Left Handed Shaft, andRight Handed Shaft. The analysis has been done for each subsystem by computing thecharacteristic of the maintenance system i.e: reliability, failure rate, mean time between failure,availability, failure cost, preventive cost, and replacement interval time. Furthermore it can becreate the optimum scheduling of preventive maintenance. Based on analysis of reliability,availability, failure rate, production lost cost, and maintenance cost, obtained the replacementinterval time of subsystems i.e: Left & Right Handed Worm = 76 days, Bushing = 76 day , PressCylinder = 95 days, Rebuild Worm = 95 days, Bearing SKF 29326 = 228 days, Left HandedShaft =114 days, and Right Handed Shaft = 76 days. The optimum maintenance schedulingwas modified based on replacement interval time of subsystem. Analysis of the new schedulingshows that the reliability of Screw Press(1) can be improve from 0.4207 to 0,8259, ScrewPress(2) from 0,4024 to 0,8259, Screw Press(3) from 0,4504 to 0,8259, and Screw Press(4)from 0,4204 to 0,8259 respectively. The availability of Screw Press(1) improved from 0,8564 to0,9524, Screw Press(2) from 0,9201, to 0,9524, Screw Press(3) from 0,8585 to 0,9524, andScrew Press(4) from 0,875 to 0,9524. The probability of failure frequency of Screw Press (1) isreduced from 37 to 19, Screw Press (2) from 23 to 19, Screw Press(3) from 25 to 19, and ScrewPress(4) from 23 to 19. This study shows that the reliability and availability analysis is veryuseful for deciding maintenance intervals, planning and organizing maintenance.Keywords: Reliabilit; Availabilit; Crew pres, Scheduling.